2011
DOI: 10.1103/physrevd.83.114009
|View full text |Cite
|
Sign up to set email alerts
|

Strong coupling constants of bottom and charmed mesons with scalar, pseudoscalar, and axial vector kaons

Abstract: The strong coupling constants, gD(s)DK(0)*, gB(s)BK(0)*, gD(s)*DK, gB(s)*BK, gD(s)*DK1 and gB(s)*BK(1), where K(0)*, K and K(1) are scalar, pseudoscalar, and axial-vector kaon mesons, respectively, are calculated in the framework of three-point QCD sum rules. In particular, the correlation functions of the considered vertices when both B(D) and K(0)*(K)(K(1)) mesons are off shell are evaluated. In the case of K(1), which is either K(1)(1270) or K(1)(1400), the mixing between these two states are also taken int… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 60 publications
3
17
0
Order By: Relevance
“…Besides, in Ref. [11] it was shown that the gluon condensate contribution to the D * Dπ and J /ψD * D vertices was negligible, as compared with the perturbative contribution. For these reasons, we do not include the gluon condensate and higher dimension condensates in the present work.…”
Section: The Qcd Sidementioning
confidence: 97%
See 2 more Smart Citations
“…Besides, in Ref. [11] it was shown that the gluon condensate contribution to the D * Dπ and J /ψD * D vertices was negligible, as compared with the perturbative contribution. For these reasons, we do not include the gluon condensate and higher dimension condensates in the present work.…”
Section: The Qcd Sidementioning
confidence: 97%
“…In the case of K off-shell meson, we use, as usual in QCDSR, the pseudoscalar current for it, see Refs. [6] (D * Dπ), [13] (D * s DK) and [11] (B * s BK). The general expression for the vertices has different structures, which can be written in terms of a double dispersion relation over the virtualities p 2 and p 2 , holding Q 2 = −q 2 fixed:…”
Section: The Qcd Sidementioning
confidence: 99%
See 1 more Smart Citation
“…Heavy quarkonium states can have many bound states and decay channels used to study and determine different parameters of standard model (SM) and QCD from the theoretical perspective. In particular, the calculation of bottomonium masses [3], total widths, coupling constants [4][5][6][7], and branching ratio can serve as benchmarks for the low energy predictions of QCD. In addition, the theoretical calculations on the branching ratio of radiative decays of heavy quarkonium states are relatively clean with respect to the hadronic or semileptonic decays, and their comparison with experimental data could provide important insights into their nature and hyperfine interaction.…”
Section: Introductionmentioning
confidence: 99%
“…and B c B c J/ψ vertices have been studied with the three-point QCDSR [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34], while the hadronic coupling constants in the [54], analyze all the tensor structures to study the vertices D * 2 Dπ , D * s2 DK , B * 2 Bπ , and B * s2 B K with the threepoint QCDSR so as to choose the pertinent tensor structures (in this article, we choose the tensor structures g μν and p μ p ν , which differ from the tensor structure p μ p ν chosen in Ref. [55]), then we obtain the corresponding hadronic coupling constants and study the two-body strong decays…”
Section: Introductionmentioning
confidence: 99%